LncRNA RP11-499E18.1 Inhibits Proliferation, Migration, and Epithelial–Mesenchymal Transition Process of Ovarian Cancer Cells by Dissociating PAK2–SOX2 Interaction - Yang, Juan; Peng, Shuping; Zhang, Keqiang (Frontiers in Cell and Developmental Biology, 2021)
Backgrounds: Ovarian cancer is one of the most common and deadly gynecological malignancies worldwide. It’s urgent to identify diagnostic biomarkers of OC to disclose the underlying mechanism. Methods and materials: Bioinformatics analysis were used to identify potential lncRNA, mRNA and target gene. The expression of RP11-499E18.1, PAK2 and SOX2 were detected using qRT-PCR. The interaction between RP11-499E18.1 and PAK2, as well as PAK2 and SOX2 were respectively determined using RNA pulldown, RIP and co-IP assay. Cell transfection was employed to alter the expression of RP11-499E18.1, PAK2 and SOX2. Localizations of RP11-499E18.1, PAK2 and SOX2 were respectively determined employing IHC, IF and FISH. The regulatory effects of RP11-499E18.1, PAK2 and SOX2 on OC cell proliferation, migration, colony formation, expression of EMT-related factors and SOX2 nuclear translocation were determined. Finally, the effects of RP11-499E18.1 and PAK2 expression on the tumor growth in nude mice were determined. Results: RP11-499E18.1, PAK2 and SOX2 were selected in our study. RP11-499E18.1 was down-regulated in OC tissues, while PAK2 and SOX2 was upregulated. RP11-499E18.1 exists in cells in the form of plasma-nucleus coexistence. RP11-499E18.1 overexpression suppressed cell proliferation, migration and expression of EMT-related Vimentin, lessened nuclear translocation of SOX2 and inhibited tumor growth in nude mice. However, these effects were notably reversed by PAK2 upregulation, and eventually offset by SOX2 knockdown. RP11-499E18.1 overexpression reduced the interaction between PAK2 and SOX2, as well as the phosphorylation of SOX. Conclusions: These evidences demonstrated that RP11-499E18.1 might suppress the progression of OC via dissociating the interaction between PAK2 and SOX2.